2018
DOI: 10.1080/10245332.2018.1435046
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of Mda-7/IL-24 and high expression of C-myb in tumour tissues are predictors of poor prognosis for Burkitt lymphoma patients

Abstract: Mda-7/IL-24: melanoma differentiation associated gene7/interleukin 24; FCM: flow cytometry; Ecog: Eastern Cooperative Oncology Group; IPI: International lymphoma prognosis index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Ma et al found that high expression of c‐Myb was associated with advanced clinical stage and worse OS/progression‐free survival in patients with diffuse large B‐cell lymphoma. They also proved its same prognostic value in patients with Burkitt lymphoma . Li et al found that a high mRNA level of c‐Myb indicated worse relapse‐free survival in patients with breast cancer, and that it can combine with interleukin (IL)‐1β to predict OS in patients who are estrogen receptor(−).…”
Section: Discussionmentioning
confidence: 95%
“…Ma et al found that high expression of c‐Myb was associated with advanced clinical stage and worse OS/progression‐free survival in patients with diffuse large B‐cell lymphoma. They also proved its same prognostic value in patients with Burkitt lymphoma . Li et al found that a high mRNA level of c‐Myb indicated worse relapse‐free survival in patients with breast cancer, and that it can combine with interleukin (IL)‐1β to predict OS in patients who are estrogen receptor(−).…”
Section: Discussionmentioning
confidence: 95%
“…The oncogenic roles of transcription factor MYB have been widely studied in different types of cancer including leukemia, colon and breast cancer and adenoid cystic carcinoma (55)(56)(57). Overexpression of MYB has been reported to be associated with poor prognosis in leukemogenesis (58), colorectal (59) and breast cancer (60) and Burkitt lymphoma (61). Therefore, DDX41 may function in tumorigenesis by regu-lating the expression levels of certain oncogenes and tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…It was well accepted that IL-24 mediated cancer cell-specific death and apoptosis via multiple signaling pathways (21)(22)(23). Significantly lower IL-24 expression predicted poorer prognosis in lung adenocarcinoma (24), breast cancer (25), head and neck squamous cell carcinoma (26), and lymphoma (27,28). IL-24 high adenocarcinoma patients showed a notably higher incidence of apoptotic tumor cell death, and displayed favorable post-therapy prognosis as compared with IL-24 low patients (24).…”
Section: Discussionmentioning
confidence: 99%